ANALYSIS OF HALAL SUPPLY CHAIN MANAGEMENT IN FRIED CHICKEN RESTAURANT USING SUPPLY CHAIN OPERATION REFERENCE (SCOR) 12.0 - Auliya Hayyu Ratnaningtyas; Qurtubi; Elisa Kusrini; Rahma Fariza (Journal of Industrial Engineering and Halal Industries, 2022)
As a country with the largest Muslim population, Indonesia must be able to compete with the halal industry. Food products are one of the important aspects in the halal industry. One of the food providers that is mushrooming a lot today is fast food restaurants. In this regard, fast food restaurants must be able to guarantee that the products provided are guaranteed to be hallowed. One of the fast-food restaurants located in Yogyakarta is XYZ restaurant. This study aims to determine the performance of halal supply chain performance in restaurants to help restaurants in improving performance so that they can compete in the halal industry. The methods used in this study are Supply Chain Operation Reference (SCOR) 12.0, Analytical Hierarchy Process (AHP), and Traffic Light System. It was found that there were 44 metrics with 4 of them based on Islamic values. There are 2 metrics with marginal categories and 9 metrics with unsatisfactory categories. Overall, it was found that the restaurant's performance value was 67.65% with a marginal or average category.